Perancangan Turbin BULB Poros Vertikal - Prayudi Prayudi; Fitra Fauzan (Sekolah Tinggi Teknik - PLN, 2015)
PLTMH is power plants, now many in developing good in the village or in isolated areas. One of the type of turbine that potential to PLTMH on the river - river in Indonesia is turbine Bulb. Turbine Bulb is a kind turbine Kaplan who has been developed, turbine was in use on the head with a low efficiency. The